Efektivitas farmakologis jahe (Zingiber officinale) terhadap preferensi masyarakat dalam penggunaannya sebagai obat herbal - Azzahra, Ainna Selila (Maliki Interdisciplinary Journal, 2026)
Ginger (Zingiber officinale) is one of the herbal plants widely used by the community as traditional medicine and complementary therapy. The increasing use of ginger is driven not only by cultural factors but also by scientific evidence demonstrating its effectiveness and safety. This article aims to review the mechanism of action of ginger’s active compounds, its pharmacological effectiveness based on research findings, and factors influencing public preference in using ginger as herbal medicine. This study employed a literature review method by analyzing relevant national and international scientific articles. The results indicate that the main bioactive compounds of ginger, such as gingerol, shogaol, zingerone, and paradol, exhibit anti-inflammatory, antioxidant, analgesic, antimicrobial, and immunomodulatory activities through inhibition of inflammatory pathways and enhancement of antioxidant defense systems. Furthermore, public preference for ginger use is influenced by scientific, psychological, socio-cultural, and economic factors. Therefore, ginger has significant potential as an effective and relatively safe herbal medicine, although its use should be supported by scientific evidence and proper education.